Gender Differences in Anxiety and Depression amongst Bangladeshi Medical Students - Sanzana, Lamia; Cooke, Anne; Parvin, Shamima; Ahmed, Sohaila; Nurunnabi, Abu Sadat Mohammad (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Evidence suggests that medical students experience higher rates of anxiety and depression than that of general population. Objective: This study aims to quantitatively assess the level of anxiety and depression amongst male and female medical students of Bangladesh. Methods: This cross-sectional, descriptive study was conducted in three government medical colleges in Dhaka, Bangladesh, between June 2022 and June 2023. A total of 262 medical students (99 males and 163 females) participated in this study. The Generalized Anxiety Disorder 7-item (GAD-7) was used to assess the level of anxiety, while assessment of the level of depression was done using the Patient Health Questionnaire (PHQ-9). Results: Among 262 medical students, all of them were between 18 and 22 years; male-female ratio was 1:1.65. Among them, 213(81%) had some level of anxiety. 27(17%) female and 22(22%) male students had minimal level of anxiety (al1). 50(31%) female and 45(45%) male students had mild anxiety (al2), while 44(27%) female and 23(23%) male students had moderate level of anxiety (al3). However, moderately severe level of anxiety (al4) was observed in 42(26%) female and 9(9%) male students. Significant difference was found in the level of anxiety between male and female medical students (p=0.002). A total of 231(88%) had some level of depression. None to minimal level of depression (dl1) was found in 22(13%) female and 9(9%) male students. Mild level of depression (dl2) was observed in 50(31%) female and 39(39%) male students, while moderate level of depression (dl3) was observed in 53(33%) female and 36(36%) male students. Moreover, moderately severe (dl4) level of depression was evident in 30(18%) female and 11(11%) male students. However, severe level of depression (dl5) was detected in only 8(5%) female and 4(4%) male students. However, no significant difference was observed in the level of depression between male and female medical students (p=0.313). Conclusion: Our data suggests a significant difference in anxiety levels between male and female medical students and no difference in depression levels between them. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 180-184